Agency, Trust and Blame in Decision-Making Algorithms: An Analysis of Twitter Discourses - Heaton, Dan (2024)
This PhD project focuses on exploring the concepts of agency, blame and trust concerning public-facing decision-making algorithms through an interdisciplinary linguistic approach. Public-facing decision-making algorithms, such as the algorithms underpinning A Level grade calculations in 2020, the NHS Covid-19 contact tracing app and ChatGPT, have increasingly impacted global conversations, yet concerns have emerged regarding their perceived social agency, particularly when negative outcomes arise. Determining responsibility and accountability for these outcomes is challenging due to the complex and opaque nature of how these algorithms are designed and deployed. Trust in such systems is vital for the future development of artificial intelligence technologies, emphasising the need for algorithms to be perceived as trustworthy by design and in practice. Despite this, little exploration exists regarding how trust and blame are influenced by the perceived agency, responsibility and accountability of these systems. By analysing Twitter discourses, where views have been expressed about the three aforementioned public-facing decision-making algorithms, this research aims to provide nuanced insights into how these systems are perceived in society.